To the Arctic by canoe, 1819-1821 : the journal and paintings of Robert Hood, midshipman with Franklin - Hood, Robert, 1797-1821 (McGill-Queen's University Press, 1994)
"To the Arctic by Canoe records the experiences of a remarkable young adventurer, Robert Hood, during the first overland Arctic expedition led by Sir John Franklin. Franklin's expedition was the first to travel the northern coast of North America's Arctic; in two birch-bark canoes the party surveyed no less than 675 miles of Arctic coastline." "When supplies ran out, the return trek across the Barrens became one of the most tragic incidents in the history of Arctic exploration. Hood was one of those who perished on this trip. Weakened by starvation, he was shot through the head by a member of the party turned cannibal." "A highly sensitive and educated man with a painter's eye for detail, Hood was an astute observer of the political and social ways of the North. His journal reveals his awareness, unusual in his time, of the adverse effects of the coming of the Europeans on Native peoples and their environment. Hood's paintings capture the beauty as well as the harshness of the North. His bird paintings in particular are of special artistic and historical interest. Book jacket."--Jacket